2010
DOI: 10.1007/s00726-010-0802-1
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecificity of isotopic exchange of C-α-protons of glycine catalyzed by three PLP-dependent lyases: the unusual case of tyrosine phenol-lyase

Abstract: A comparative study of the kinetics and stereospecificity of isotopic exchange of the pro-2R- and pro-2S protons of glycine in (2)H(2)O under the action of tyrosine phenol-lyase (TPL), tryptophan indole-lyase (TIL) and methionine γ-lyase (MGL) was undertaken. The kinetics of exchange was monitored using both (1)H- and (13)C-NMR. In the three compared lyases the stereospecificities of the main reactions with natural substrates dictate orthogonal orientation of the pro-2R proton of glycine with respect to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…To determine the stereospecificity of these transfers, we expressed PhnJ in minimal media that was supplemented with glycine that was specifically deuterated at the proR position. The monodeuterated glycine was made by incubating glycine with the enzyme methionine-γ-lyase (MGL) in the presence of D 2 O (Koulikova et al, 2011). This reaction is illustrated in Scheme 6.…”
Section: Stereospecific Hydrogen Atom Transfersmentioning
confidence: 99%
“…To determine the stereospecificity of these transfers, we expressed PhnJ in minimal media that was supplemented with glycine that was specifically deuterated at the proR position. The monodeuterated glycine was made by incubating glycine with the enzyme methionine-γ-lyase (MGL) in the presence of D 2 O (Koulikova et al, 2011). This reaction is illustrated in Scheme 6.…”
Section: Stereospecific Hydrogen Atom Transfersmentioning
confidence: 99%
“…Reaction of Methionine ␥-Lyase with Glycine-It was shown that MGL catalyzes exchange of both C␣-protons of glycine with high stereospecificity for pro-R-proton, which reacts by a factor of 1440 faster than does pro-S-proton (35). In principle, the exchange may proceed through the formation of a quinonoid intermediate or by a concerted mechanism implying fast and reversible transfer of the pro-R-proton from C␣ atom to C4Ј atom or a formation of a six-membered transition state incorporating a water molecule (36) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The rate and the equilibrium constants calculated using Scheme 3 are listed in Table 2. The steady-state rate constant (k ex ) of the isotopic exchange of the two enantiotopic protons of glycine (35) are also presented in Table 2. Having compared the exchange rates with the other rates in Table 2, it was supposed that the complex (E⅐Gly) 1 , which absorbs at 420 nm and is formed in a millisecond time interval, probably corresponds to the external aldimine intermediate with orthogonal orientation of the "right" pro-R-proton (H r ) to the cofactor plane (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Растворитель удаляли на роторном испарителе. Для определения конфигурации у C-α-атома дейтерированный продукт был превращен в дипептид, L-фенилаланил-[D]-глицин в реакции с Boc-L-Phe-ONp [40,41]. Дипептид растворяли в 0.5 мл D 2 O, и 1 Н-ЯМР-спектр записывали на спектрометре Вruker AMXIII-400 с рабочей частотой 400 МГц.…”
Section: изотопный обмен C-α-и C-β-протонов ингибиторов в комплексах ...unclassified